Mechanistic loop-resolution strategies for short-type single-balloon enteroscopy-assisted ERCP in patients post Roux-en-Y hepaticojejunostomy with a preserved stomach and duodenum - Yang, Min Jae; Cho, Woohyun; Hwang, Jae Chul; Yoo, Byung Moo; Kim, Soon Sun; Kim, Jin Hong; Shin, Eun Ji (Endoscopy, 2025)
Endoscopic access in Roux-en-Y hepaticojejunostomy after bile duct resection is more challenging than Roux-en-Y reconstruction following gastrectomy or pancreaticoduodenectomy owing to unstable S-shaped loop formation across the preserved upper gastrointestinal structure. This study evaluated the feasibility of mechanistic loop-resolution strategies for short-type single-balloon enteroscopy (short SBE)-assisted endoscopic retrograde cholangiopancreatography (ERCP) in patients post Roux-en-Y hepaticojejunostomy with a preserved stomach and duodenum.Mechanistic loop resolution converted an S-shaped loop with two conflicting rotational vectors into a unidirectional rotational vector, forming either a J configuration or a ring-shaped loop.The short SBE approach was successful in 27 of 31 cases (87.1%). The mean time to reach the jejunojejunal and hepaticojejunal anastomoses was 24.3 minutes and 61.8 minutes, respectively. Biliary cannulation via the hepaticojejunostomy was successful in 96.6% of cases. The therapeutic success rate was 83.9% (26/31) for short SBE and 84.8% (28/33) when including both short and long SBE. The mean total procedure time was 95.9 minutes. Adverse events occurred in three patients (9.1%).Standardized mechanistic loop-resolution strategies yielded high success rates for the short SBE approach and ERCP in patients with a Roux-en-Y hepaticojejunostomy and a preserved stomach and duodenum.